2001
DOI: 10.1590/s0004-282x2001000600002
|View full text |Cite
|
Sign up to set email alerts
|

Dosage of lactate in the cerebrospinal fluid in infectious diseases of the central nervous system

Abstract: -This paper analyzes the diagnosis aid of the dosage of lactate in the cerebrospinal fluid (CSF) in infectious diseases of the central nervous system (CNS). We analyzed prospectively 130 samples of CSF of 116 patients with diagnoses of infectious processes in the CNS. The 130 samples of CSF were divided into five groups: 28 samples of the control group, 40 of bacterial meningitis, 22 of viral meningitis, 16 of fungal meningitis and 24 of patients presenting acquired immune deficiency syndrome (AIDS). The conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
1
5
1
1
Order By: Relevance
“…We found similar results for lactate (0.96, range: 0.93-1.00). Our study showed that CSF lactate was also effective in distinguishing between CSF samples taken while on antibiotic therapy, when CSF cultures were negative; a finding also published in the report by Cunha [19] and suggested by other authors [24,25].…”
Section: Discussionsupporting
confidence: 88%
“…We found similar results for lactate (0.96, range: 0.93-1.00). Our study showed that CSF lactate was also effective in distinguishing between CSF samples taken while on antibiotic therapy, when CSF cultures were negative; a finding also published in the report by Cunha [19] and suggested by other authors [24,25].…”
Section: Discussionsupporting
confidence: 88%
“…14 In this study, it was observed that the leucocyte count in the bacterial meningitis was in the range 144 to 7200 cells/mm 3 . No significant correlation was identified between CSF lactate level and CSF leucocytes in bacterial meningitis in this study, whereas in the study by Cabeca H L et al, 15 a positive correlation was found between CSF lactate levels and cellularity in CSF. CSF protein in the bacterial meningitis in this study was in the range of 50-350 mg/dL.…”
Section: Discussioncontrasting
confidence: 86%
“…The lactate is not specific for tuberculous meningitis but is a good marker of cerebral metabolism in bacterial and fungal meningitis. It has no influence of blood concentration, as occurs with the glucose, and is a product of glucose metabolism in CSF 9 . Atypical findings in the CSF such as a concentration of neutrophils and normal exam results may contribute to making the diagnosis more difficult 7 .…”
Section: Discussionmentioning
confidence: 99%